Bypassing Health Providers : The Quest for Better Price and Quality of Health Care in Chad - Gauthier, Bernard; Wane, Waly (World Bank, Washington, DC, 2012)
This paper investigates individuals' bypassing behavior in the health sector in Chad and the determinants of individuals' facility choice. The authors introduce a new way to measure bypassing using the patients' own knowledge of alternative health providers available to them instead of assuming that information as previously done. The authors analyze how perceived health care quality and prices impact patients' bypassing decisions. The analysis uses data from a Quantitative Service Delivery Survey in Chad's health sector carried out in 2004. The survey covers 281 primary health care centers and 1,801 patients. The matching of facility data and patient data allows the analysis to control for a wide range of important patient and facility characteristics, such as income, severity of illness, quality of health care, or price of services. The findings show that income inequalities translate into health service inequalities. There is evidence of two distinct types of bypassing activities in Chad: (1) patients from low-income households bypass high-quality facilities they cannot afford to go to low-quality facilities, and (2) rich individuals bypass low-quality facilities and aim for more expensive facilities that also offer a higher quality of care. These significant differences in patients' facility choices are observed across income groups as well as between rural and urban areas.